2007
DOI: 10.1016/j.bbamem.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Phase studies of model biomembranes: Macroscopic coexistence of Lα+Lβ, with light-induced coexistence of Lα+Lo Phases

Abstract: Phase diagrams of 3-component lipid bilayer mixtures containing cholesterol reveal major differences among the different types of lipids. Here we report that mixtures of cholesterol together with POPC and a high-melting temperature PC or sphingomyelin show different phase behavior from similar mixtures that contain DOPC or di-phytanoyl-PC instead of POPC. In particular, only one region of macroscopic phase coexistence occurs with POPC, a region of coexisting liquid disordered and solid phases, {Lalpha+Lbeta}. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
175
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(186 citation statements)
references
References 25 publications
(39 reference statements)
10
175
1
Order By: Relevance
“…Several studies have revealed the formation of temperature-and concentrationdependent dense domains or "patches" in phospholipid bilayers surrounding lipid-rich aggregates (29)(30)(31)(32). These patches were reported to alter the structure of biological cell membranes (33) and potentially regulate cell signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the formation of temperature-and concentrationdependent dense domains or "patches" in phospholipid bilayers surrounding lipid-rich aggregates (29)(30)(31)(32). These patches were reported to alter the structure of biological cell membranes (33) and potentially regulate cell signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Also of interest for the behavior of cell membranes, even single phase nonideal lipid mixtures can be induced to increase the size of their heterogeneities. Here, a case that plagues the use of fluorescence microscopy is the introduction of artifactual visible domains by intense illumination (Zhao et al 2007b). This might be caused by free radical initiated polymerization that starts from the reactive excited singlet state (Ayuyan and Cohen 2006).…”
Section: Discussionmentioning
confidence: 99%
“…4 The particular contribution cholesterol makes in the structure of rafts is to facilitate the formation and maintenance of a liquid-ordered (L o ) membrane domain. 5,6 While the majority of experimental studies have involved dipalmitoyl or dimyristoyl phosphatidylcholine (DPPC or DMPC) [7][8][9][10] there are also experimental studies on the effect of cholesterol on palmitoyl-oleyol phosphatidylcholine (POPC). [11][12][13][14][15][16][17][18] Hyslop et al 11 utilized fluorescence depolarization to estimate that cholesterol molecules in a 1:1 POPC:cholesterol bilayer remain separated with a minimum separation distance of ∼10 Å.…”
Section: Introductionmentioning
confidence: 99%
“…POPC has also been investigated as part of ternary bilayer mixtures with sphingomeylin and cholesterol 8,20,21 or ceramide. 22 Heerklotz and co-workers used calorimetry to compare the interactions of cholesterol with large unilamellar vesicles of POPC plus 30% cholesterol, sphingomyelin plus 30% cholesterol, and 1:1 sphingomyelin:POPC plus 30% cholesterol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation